2008
DOI: 10.1097/mnm.0b013e328308e079
|View full text |Cite
|
Sign up to set email alerts
|

The additive clinical value of combined thyroglobulin and antithyroglobulin antibody measurements to define persistent and recurrent disease in patients with differentiated thyroid cancer

Abstract: Combined Tg-TgAb values were found more useful than only Tg for recurrent and persistent diseases. Combined Tg and TgAb measurements seemed to be a useful marker.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 14 publications
0
10
0
Order By: Relevance
“…Chung et al considered a serum TgAb level below 100 U/ml as negative, and found elevated TgAb levels in 22AE6% of DTC patients after ablation. 10,15 Recently, Aras et al 17 reported that the optimal threshold value for TgAb was 27AE8 IU/ml. TgAbs remained detectable in 44AE2% at 6-12 months after therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Chung et al considered a serum TgAb level below 100 U/ml as negative, and found elevated TgAb levels in 22AE6% of DTC patients after ablation. 10,15 Recently, Aras et al 17 reported that the optimal threshold value for TgAb was 27AE8 IU/ml. TgAbs remained detectable in 44AE2% at 6-12 months after therapy.…”
Section: Discussionmentioning
confidence: 99%
“…This occurrence of TgAb is uncorrelated with abnormal TSH levels, which indicates that it may not be necessary to test for TgAb and TPOAb in the general thyroid autoimmunity screening, as TPOAb testing alone seems sufficient [10]. In those individuals with indications of autoimmune thyroid disease (AITD), however, there is evidence that testing for both TPOAb and TgAb is beneficial [11, 12]. We only refer to TPOAb in this analysis.…”
Section: Introductionmentioning
confidence: 99%
“…Several attempts have been made to address this issue. For instance, Aras et al 12. showed that combined Tg and TgAb measurements were more informative than Tg only for recurrent and persistent DTC patients.…”
mentioning
confidence: 99%